PENERAPAN MODEL AUDITORY INTELECTUALLY REPETITION (AIR) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA - Yudi Budianti; Arrahim Arrahim; Rizki Nur Annisa (Hipotenusa Journal of Research Mathematics Education (HJRME), 2024)
The research aims to evaluate the effectiveness of the Auditory Intellectually Repetition (AIR) model in improving understanding of mathematical concepts in fifth grade elementary school students. The subjects of this research were fifth grade students at SDN Bahagia 01, consisting of 29 students, with details of 13 male students and 16 female students. The research instrument given was a test consisting of 10 descriptive questions. The results of data analysis are (1) Percentage of classical completeness, (2) Indicator values. From this data, it can be concluded that the use of the Auditory, Intellectually, Repetition (AIR) model has proven effective in increasing the understanding of mathematics concepts for class V students. Significant increases in the percentage of classical completeness and the average score of students between cycle I and cycle II, in the cycle I was 58.6% with an average student score of 71.6. And in cycle II there was an increase with a classical completion percentage of 86.2% with an average student score of 89. This shows that the Auditory, Intellectually, Repetition (AIR) model is effective in helping students achieve a better understanding of the mathematical concepts being taught. The existence of the Auditory, Intellectually, Repetition (AIR) model can increase the understanding of mathematics concepts for fifth grade students at SDN Bahagia 01 Bekasi Regency by 27.6%.